Development of a protocol for determining confined space occupant load. Issue 2 (30th July 2013) - Wilson, Peg; Wang, Qingsheng
<x xml:space="preserve">Abstract</x> Working in confined spaces such as storage tanks always poses significant challenges for all workers even with the existing Occupational Safety and Health Administration standard (29 CFR 1910.146). In the process industries, confined space operation requires its own set of safety considerations. One of the biggest challenges is how to determine the proper occupant load of a hazardous confined space. It is an issue that needs to be addressed to ensure the emergency preparedness and safety of workers who enter confined spaces. Occupant load can be determined through a number of different variables, including exit size, distance to opening, internal structures, and ratings of hazards involved with the confined space. No current field‐ready calculation tool could take into account these variables when determining a confined space occupant load. In this work, an easy to use field worksheet was developed that would quickly determine the occupant load of a given confined space. The worksheet could be combined with a predetermined rescue plan and appropriate safety equipment to make sure occupants are well prepared and will be evacuated in a safe manner. © 2013 American Institute of Chemical Engineers Process Saf Prog 33: 143–147, 2014